Method for producing lightweight concrete mixes using lightweight aggregates

A two-step mixing process with high-speed and low-speed stirring effectively addresses the challenges of producing lightweight concrete with low particle strength and bulk density, achieving superior compressive strength, thermal insulation, and sound insulation, while minimizing environmental impact and transport costs.

JP2025501326AInactive Publication Date: 2025-01-17B TON IP GMBH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024540050
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2021-12-31
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional mixing processes and procedures using forced mixing and free-fall mixers fail to produce lightweight concrete with low particle strength and bulk density, resulting in increased density due to water absorption by lightweight aggregates, leading to undesirable properties such as higher shrinkage and cracking.

Method used

A two-step mixing process involving high-speed stirring to form a suspension mixture without lightweight aggregates, followed by low-speed stirring with the aggregates, using binders like cement or geopolymer, and incorporating additives to control water absorption and density, ensuring optimal water availability for the reaction.

Benefits of technology

The method produces lightweight concrete with super compressive strength, low dry bulk density, improved thermal insulation, and good sound insulation, achieving an A value of over 500, while reducing environmental impact and transport costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501326000001
    Figure 2025501326000001
  • Figure 2025501326000002
    Figure 2025501326000002
  • Figure 2025501326000003
    Figure 2025501326000003
Patent Text Reader

Abstract

The present invention provides a method for producing lightweight concrete mixes using lightweight aggregates, comprising at least a two-stage mixing process, where a suspension mixture comprising a binder composition is first prepared by high speed mixing of cement or geopolymer and water, and then the suspension mixture is mixed by low speed mixing with the lightweight aggregate components. The present invention also encompasses suitably produced lightweight concrete and lightweight concrete mixes. Candidate binder compositions include, for example:- 60-80% by weight of finely ground slag sand cement, 10-60% by weight of fly ash,- 2-25% by weight of alkali metal hydroxide / alkali metal silicate, 75-98% by weight of finely ground slag sand,- 2-20% by weight of alkali metal hydroxide / alkali metal silicate, 60-78% by weight of finely ground slag sand,- 20-38% by weight of fly ash cement, 30-50 kg / m (in lightweight concrete mix) micro-silica cement, 10-60% by weight of rice husk fly ash cement, 1-5% by weight of caustic calcined CaO / MgO, etc.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The method for producing a lightweight concrete mix using lightweight aggregate according to the present invention comprises at least a two-stage mixing process, first producing a suspension mixture comprising a binder composition by high speed stirring of cement or geopolymer and water, and then mixing the suspension mixture by low speed stirring with, inter alia, lightweight aggregate. The present invention further comprises the lightweight concrete mix and the lightweight concrete thus produced. [Background technology]

[0002] Concrete: 8N / mm 2 Measured as dry gross density with a minimum compressive strength of 2,000 kg / m 3 to 2,600 kg / m 3 Lightweight concrete has a defined relative density of 2,000 kg / m 3 Lightweight concrete is defined as concrete having a dry bulk density of less than 40 kg / m. In the case of lightweight concrete, the low density is achieved, for example, by the incorporation of lightweight aggregates. The lower the density of the lightweight aggregates, the lower the density of the lightweight concrete produced from them can be. Lightweight aggregates can have a dry bulk density of, for example, 40 to 1200 kg / m 3 It has a bulk density of.

[0003] Lightweight concrete is used to manufacture building products. Firstly, it is a building material before molding and a component after at least partial hardening. The components are manufactured to be permanently installed in a physical structure. Structures manufactured from building materials and components, manufactured to be connected to the ground, such as buildings, are building products as well. The buildings can also be prefabricated houses, prefabricated garages and silos, or so-called "temporary structures" suitable for repeated construction in different locations, temporary construction and dismantling again. Typical components are lightweight concrete wall elements or lightweight concrete ceiling elements or lightweight concrete bricks.

[0004] 2~100N / mm 2 The components, which have a compressive strength of more than 1000 g / m² (according to DIN EN 1520, DIN 4213, DIN EN 206-1 or DIN 1045-2), can be adapted in different ways to different construction requirements.

[0005] Lightweight concrete is suitable for exterior and interior walls, from basements to roofs, for apartment buildings, as well as agricultural, public, or industrial buildings and bridges. Lightweight building slabs and the like for insulation purposes or fire protection etc. can also be made from lightweight concrete, but their compressive strength may also be lower.

[0006] Components made of lightweight concrete have a high ratio of compressive strength to dry bulk density. The dimensionless so-called A-number is obtained from the calculation relationship of compressive strength to dry bulk density. The A-number is described in Siegfried G. Zurn, "Einfluss der Sandminerale auf die Bildung von Calciumsilikathydraten (CSH-Phasen), das Gefuge und die mechanischen Eigenschaften von Porenbetonprodukten", Logos-Verlag, Berlin, 1997. It represents the relative compressive strength. The higher the A-number, the better the level of compressive strength. The A-number is calculated as follows: A value = Compressive strength (N / mm 2 ): [Dry bulk density (kg / dm 3 ) 2 0.016]

[0007] The lower mass of components or building materials, for example when transported by truck or ready-mix concrete truck, respectively, simplifies and reduces the costs of transportation to the construction site, reduces CO2 emissions due to the additional loading capacity, and provides for fast and precise work. In particular, prefabricated components made of lightweight concrete (which can be produced in factories with integrated supply lines), doors and windows, as well as finishing surfaces, allow short construction periods to be achieved. Furthermore, the lightweight elements can also be transported to construction sites in difficult locations.

[0008] In the case of components, the heavier the mass, the higher the sound insulation index: despite their very light mass, components made of lightweight concrete have high sound absorption, i.e. good soundproofing capacity.

[0009] The absorbency and therefore the suction behavior of lightweight aggregates have an impact when they are used as aggregates in lightweight concrete. The higher and faster the water absorption, the more problematic the impact of the behavior during the production of lightweight concrete can be, since water is removed from the mixture and is therefore no longer available for binding and workability.

[0010] In fact, there has been no shortage of attempts to use lightweight aggregates with low bulk density and particle strength for use in building materials such as wall and ceiling elements and bricks. To date, such uses have been unsuccessful, especially due to the high absorption capacity of these lightweight aggregates, which leads to the removal of water from the cement when they are mixed simultaneously with the cement. Low particle strength is problematic, since when mixed in an industrial standard concrete mixer, the lightweight aggregates break down during the mixing process, resulting in a larger surface area, which in turn further increases the water and binder requirements, which in turn unintentionally increases the density of the final product, in addition to other undesirable properties such as higher shrinkage and risk of cracking. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] DE 10354888 B4 [Patent Document 2] DE 102011102988 A1 [Patent Document 3] EP 0808959 B1 [Non-patent literature]

[0012] [Non-Patent Document 1] Siegfried G. Zurn, "Einfluss der Sandminerale auf die Bildung von Calciumsilikathydraten (CSH-Phasen), das Gefuge und die mechanischen Eigenschaften von Porenbetonprodukten", Logos-Verlag, Berlin, 1997 Summary of the Invention [Problem to be solved by the invention]

[0013] The present invention relates to a lightweight concrete for producing building products, which can be produced using lightweight aggregates having low particle strength and bulk density, and has a concrete strength of 200 kg / m 3 ~1999kg / m 3 Dry bulk density (measured according to DIN EN 12390-7 in a heating cabinet at 105 °C) and 0.5 N / mm 2 ~100N / mm 2 The objective of the present invention is to provide a lightweight concrete having a compressive strength of .

[0014] Components made of lightweight concrete are intended to have a low dry bulk density, improved thermal insulation values ​​and very good sound insulation values, as well as a high final strength compared to the density, with an A-number of over 500 depending on the production type.

[0015] For CO2 reduction, the binder is for use in the production of lightweight concrete, such as geopolymers, or cement with low clinker content and low content of alternative materials such as ground blast furnace slag. [Means for solving the problem]

[0016] To date, this goal has not been achievable with conventional mixing processes and procedures using known forced mix and free fall mixers.

[0017] The objects of the invention are defined in the independent claims. Preferred embodiments are the subject of the dependent claims or are described below. In addition to the production of lightweight concrete mixes and lightweight concrete, the invention also relates to lightweight concrete mixes and lightweight concrete hardened in a mould.

[0018] A method for producing a lightweight concrete mix comprises at least the following steps: (A) combining at least water and a binder composition, particularly in the absence of lightweight aggregates, and mixing with a high speed agitating tool to form a suspension mixture; The binder composition includes at least a cement or a geopolymer as a binder, and the binder composition is added by adding water first and mixing, the weight ratio of water to binder composition in the suspension mixture is from 1:5 to 1:1, in particular from 1:2 to 2:3; the binder comprises at least 40% by weight, preferably at least 50% by weight, of the binder composition; The binder is added as a powdered solid; Process; (B) combining the slurry mix or a portion of the slurry mix with at least the lightweight aggregate or a portion of the lightweight aggregate and mixing with a low speed mixing tool to form a lightweight concrete mix; Preferably, at least the lightweight aggregate is added first and the suspension mixture is added by mixing; Lightweight aggregate: 40 to 1000 kg / m 3 , preferably 50 to 500 kg / m 3 , especially 60-300kg / m 3 and having a bulk density of The mixing with the high speed stirring tool is performed at a peripheral speed that is more than three times the peripheral speed of the mixing with the low speed stirring tool; and / or according to another definition, Mixing with high speed stirring tools is carried out at Froude numbers greater than 10, particularly greater than 25, and mixing with low speed stirring tools is carried out at Froude numbers less than 2.5, particularly less than 1.5; Process Includes.

[0019] Steps A and B are performed by mixing with different mixing energy inputs, i.e., a high speed stirring tool (A) and a low speed stirring tool (B).

[0020] Step A is preferably carried out for example for 60 to 360 seconds, in particular for 120 to 240 seconds (starting after addition of the cement / geopolymer) and independently therefrom step B is carried out for at least 120 seconds, in particular for 180 to 360 seconds (starting after addition of the suspension mixture).

[0021] The "mixed water" is first contacted with the cement or geopolymer, respectively (which in this manner includes further substances of the binder composition) and "unlocked" by mixing with a high speed stirring tool to obtain a suspension mixture before the lightweight aggregate, which is generally absorbent, is contacted with the mixed water. The lightweight aggregate is then contacted with the suspension mixture. Surprisingly, it has been found that the water is better available for the water-cement reaction or the geopolymer-water reaction, respectively, and the lightweight aggregate no longer competes for the availability of water. Taken together, as a result, less water can be used.

[0022] The method according to the invention comprises at least two mixing processes: - mixing water and a binder composition comprising at least cement or a geopolymer in the absence of lightweight aggregate to produce a suspension mixture; and - combining said suspension mixture with at least lightweight aggregates and mixing to obtain a lightweight concrete mixture; The binder or binder composition, respectively, is preferably added only to the suspension mixture.

[0023] After mixing in step A, the suspension mixture has a fluidity of at least F6. Preferably, 22-40% by weight of water is added to the suspension mixture or the suspension mixture preferably contains 22-40% by weight of water, respectively.

[0024] The binder composition for producing the suspension mixture is - cement as binder and fly ash as binder additive, in particular from 10 to 60% by weight based on the binder composition; - 30-50% by weight of cement as a binder and microsilica as a binder additive, especially for lightweight concrete mixtures; - cement as binder and rice husk fly ash as binder additive, prepared by grinding, in particular in an amount of 10 to 60% by weight based on the binder composition Alternatively, the binder composition may be a geopolymer comprising 2-25% by weight of alkali hydroxide and / or alkali silicate and 75-98% by weight of ground blast furnace slag, or 2-20% by weight of alkali hydroxide and / or alkali silicate and 60-78% by weight of ground blast furnace slag and 20-38% by weight of fly ash.

[0025] The following can be provided initially or added during preparation of the suspension mixture: rock powder as a filler, in particular with a particle size of 0.001 mm to 0.1 mm, preferably at most 0.063 mm, and / or - 0.1 to 4% by weight, preferably 0.5 to 2% by weight, of a plasticizer.

[0026] Filler in the form of rock powder and / or rock particles 0-2 mm is added, then mixing, preferably with a high-speed stirring tool, is preferably carried out temporarily, preferably at a Froude number of more than 50, in particular more than 100, in particular for at least 30 seconds, particularly preferably for at least 60 seconds, preferably the rock powder is added at a concentration of 0.01 to 0.01 cubic meter per cubic meter of the lightweight concrete mixture. 3 Preferably, rock particles 0-2 mm are added in an amount of 50-150 kg per cubic meter of the lightweight concrete mixture. 3 It is added in amounts of 100 to 500 kg per unit.

[0027] The lightweight aggregates may have a particle size in the range from 0 mm to 6 mm, in particular a particle size of 0 to 2 mm, 0 to 3 mm, 3 to 5 mm or 2 to 8 mm as particle groups, in each case in accordance with DIN EN 13055. Before the suspension mixture is added, a hydrophobizing agent can be applied to the lightweight aggregates, which can additionally or alternatively be moistened with water, in particular by spraying, before the suspension mixture is added.

[0028] The lightweight concrete is preferably 250 to 1999 kg / m 3 and, independently, an A number greater than 500.

[0029] The lightweight concrete mix can be introduced into a mold block molding machine and compacted by shaking and / or pressing to produce therefrom lightweight concrete in the form of lightweight concrete blocks.

[0030] A lightweight concrete mix may, for example, consist of the following components (based on the total mass of the lightweight concrete mix): - in the range of 10 to 90% by weight, thus for example in the range of 25 to 85% by weight or in the range of 40 to 80% by weight, etc. of the binder composition; - lightweight aggregates in the range of 1 to 50% by weight, thus also for example in the range of 5 to 30% by weight or in the range of 5 to 15% by weight; - water in the range of 20 to 40% by weight, thus also for example in the range of 20 to 35% by weight; - optionally further components in the range of 0 to 65% by weight, thus also for example in the range of 20 to 60% by weight or in the range of 10 to 30% by weight, e.g. concrete additives, etc. has.

[0031] Lightweight concrete mixtures with the addition of rock particles, in particular rock particles of 0-8 mm, have the following composition (based on the total weight of the lightweight concrete mixture): - in the range of 15 to 70% by weight, thus also, for example, in the range of 20 to 60% by weight or in the range of 25 to 55% by weight, etc. of binder; - lightweight aggregates in the range of 3 to 40% by weight, thus also for example in the range of 5 to 20% by weight or in the range of 1 to 15% by weight; - rock particles in the range of 5-65% by weight, thus also for example in the range of 20-60% by weight, in the range of 30-60% by weight or in the range of 40-60% by weight, etc.; - water in the range of 10 to 40% by weight, thus also for example in the range of 13 to 35% by weight; - if necessary, further components in the range of 0-20% by weight, thus for example in the range of 2-15% by weight, e.g. concrete additives etc. (excluding rock particles) Includes.

[0032] The lightweight aggregate can advantageously be contacted first with a portion of the suspension mixture as part of step B, preferably the lightweight aggregate is added first and then the lightweight aggregate and a further portion of the suspension mixture are added together or successively in one or several steps by mixing according to step B. This may be first subjected to a step in which 20-70% by weight, in particular 40-60% by weight, of the lightweight aggregate and 20-70% by weight, in particular 40-60% by weight, of the suspension mixture are mixed by means of a slow stirring tool according to B, followed by the addition of the remaining lightweight aggregate and the remaining suspension mixture in one or several steps by continuing the mixing by means of a slow stirring tool according to B. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] The following raw materials can be used to produce lightweight concrete mixes:

[0034] The binder composition comprises a binder and optionally a binder additive. The binder, and generally also the binder additive, is present as a powdered solid.

[0035] The binders for the method according to the invention are cement and geopolymer.

[0036] "Cement" or "cements", respectively, are inorganic finely ground substances that set and harden independently after being mixed with water as a result of a chemical reaction with the mixing water (hydraulic). From a chemical point of view, cement is mainly calcium silicate with some aluminum and iron compounds, existing as a complex mixture of substances. The raw materials for producing cement are limestone (calcium carbonate as a source of calcium oxide), clay (for silicon dioxide and aluminum oxide), sand (for silicon dioxide) and iron ore (iron(III) oxide). The raw materials are crushed and heated until they partially fuse together at the grain boundaries (sintering) and the so-called cement clinker is produced. The latter is cooled and crushed to form the final product.

[0037] Geopolymers are two-component systems consisting of reactive solids containing silicon and aluminum oxide and an alkali-based activation solution of alkali hydroxides or alkali silicates in water. Geopolymers can also be produced from ground blast furnace slag and / or fly ash or mixtures thereof, which are alkali-activated by alkali hydroxides and / or alkali silicates. The activation solution contains, for example, sodium, potassium and / or lithium water glass, particularly preferably potassium water glass.

[0038] Fly ash, ground blast furnace slag, amorphous silicon dioxide, e.g. microsilica, pozzolans (optionally together with calcium hydroxide), burnt shale, calcium and magnesium oxides, ground perlite, volcanic earth, and graphene are suitable as binder additives.

[0039] Silica dust or Microsit® (BauMineral GmbH, Herten, Germany) can be used as amorphous silicon dioxide. Pozzolans are available, for example, as finely ground perlite with a particle size of less than 45 μm.

[0040] Fly ash in the context of the present invention is, for example: silicate-rich or lime-rich dust-like particles that are deposited in electrostatic precipitators for flue gas purification of coal-fired power plants. Silica-rich fly ash consists mainly of spherical vitreous particles with pozzolanic properties and generally originates from hard coal-fired power plants. Lime-rich fly ash is a fine particulate dust with hydraulic and / or pozzolanic properties. They mainly originate from lignite-burning plants. Fly ash can also be ground more finely to increase reactivity.

[0041] Rice husk fly ash can also be used as fly ash. It can be obtained by separating the husks, also called husks, that surround the grain, from raw rice in rice mills. These husks are burned as an energy source. The ash that can be obtained in this way is rice husk fly ash, which contains a high percentage of amorphous silicon dioxide.

[0042] Blast furnace slag results when iron ore is melted in a blast furnace. Granulated blast furnace slag, a potentially hydraulic material that has solidified into a mainly vitreous form, is produced by granulation, i.e. by rapid cooling of the molten slag, which is at most 1,500 °C.

[0043] Finely ground granulated blast furnace slag, as ground blast furnace slag, can generate hydraulic properties in response to corresponding disturbances (eg, by calcium hydroxide from cement clinker).

[0044] Silica gel, silica dust or microsilica is used as a particulate solid or as a suspension in water. They consist of very fine spherical particles with a high content (more than 85% by weight) of amorphous silicon dioxide in particular. Silica dust arises as filter dust in the production of silicon or silicon alloys. The starting material for this is quartz, which is melted together with coal in an electric furnace at temperatures of more than 2500 ° C.

[0045] Pozzolans (P, Q) in the context of the present invention are substances containing silicic acid or silicic acid and alumina derived from natural sources. They are of volcanic origin (e.g. volcanic soil, lava) or are obtained from clays, slates or sedimentary rocks (phonolite). Pozzolans do not have a hardening capacity on their own. They react only when they come into contact with calcium hydroxide (e.g. derived from Portland cement clinker) after being mixed with water to form hardness-forming water-insoluble compounds. Pozzolans are used for cement production as natural pozzolans or as natural tempered (heat-treated) pozzolans (e.g. phonolite).

[0046] Burnt shale, and in particular burnt oil shale, is produced from natural shale deposits in special furnaces at temperatures of about 800° C. Finely ground burnt shale is declared to be hydraulic, but also has pozzolanic properties.

[0047] Calcium oxide (CaO) and magnesium oxide (MgO) in the context of the present invention are finely ground substances that are subjected to different calcination temperatures and fineness during production. A distinction is generally made between calcined, medium calcined (also called caustic) and hard calcined. Different reactivities, which have an impact in the context of the use according to the invention, are obtained depending on the calcination temperature. The reaction process after contact with water is, for example, rapid and severe in the case of calcination and slower in the case of medium calcination.

[0048] The use of caustic calcined products in lightweight concrete causes expansion already in the hardening stage as well as in the hardened state, thus preventing crack formation and reducing shrinkage behavior. Hard-burned materials do not achieve these properties. For this reason, only caustic calcined calcium oxide (CaO) and caustic calcined magnesium oxide (MgO) are used as binder additives according to the invention.

[0049] Finely ground perlite with a particle size of less than 45 μm is suitable as a pozzolanic additive in place of cement, especially when the water-to-cement value (W / C value) is less than 0.40, preferably less than 0.35. It has been found that it can replace up to 35% by mass of cement without incurring a loss of strength compared to mixtures with 100% by mass of cement. The replacement also has a favorable effect on the dry bulk density and shrinkage behavior, reducing both.

[0050] Graphene can also be added to the binder composition. 3 75~650g / m 3 At low loadings, the addition of graphene already results in a significant increase in strength, accelerated stiffening, and greatly reduced water absorption. Graphene is two-dimensional, but can also be added in preferred forms with several layers, for example up to 5 layers or up to 10 layers.

[0051] By adding additives, such as ground blast furnace slag, pozzolans or fly ash, it is possible to produce binder compositions with different chemical and physical properties. According to DIN EN 197-1 there are five main cement types: 1. Portland clinker cement CEM I 2. Portland composite cement CEM II 3. Blast-furnace cement CEM III 4. Pozzolana cement CEM IV 5. Composite Cement CEM V A distinction is made between 2. to 5., which represent binder compositions because they also contain ground blast furnace slag fractions or other binder additives, respectively.

[0052] All cement types listed by DIN EN 197-1 contain between 20 and 100% by weight of cement clinker.

[0053] From the point of view of environmental protection, it is particularly advantageous to use a binder composition in concrete production if the energy-intensive Portland cement clinker content is as low as possible. The lowest Portland cement clinker content is currently the case for CEM III, which is further divided into CEM III A (ground blast furnace slag content of 35-65% by mass), CEM III B (ground blast furnace slag content of 66-65% by mass) and CEM III C (ground blast furnace slag content of 81-85% by mass).

[0054] According to the prior art, a disadvantage in the production of concrete with CEM III is the significantly slower strength development compared to CEM I and CEM II, which significantly extends the shelf life in the production of prefabricated concrete parts. However, surprisingly, with the method according to the invention, an early strength is achieved which is in no way inferior to the early strength of CEM I or CEM II cements.

[0055] It is therefore preferred according to the invention to use cement or binder compositions, respectively, with a ground blast furnace slag content of more than 35% by weight, in particular more than 65% by weight, in particular CEM III A and CEM III B cements.

[0056] Mixtures of cement or binder compositions, respectively, with, for example, up to 70% by weight of fly ash and / or up to 10% by weight of microsilica, for example cements of the CEM series, can also be used. According to different designs, the cement or binder compositions, respectively, are mixed, for example, with up to 70% by weight, inter alia, of rice husk fly ash. Finely ground pozzolans can be added up to a maximum of 35% by weight.

[0057] Lightweight aggregates can in particular be used alone or in a mixture. 3 , preferably 50 to 500 kg / m 3 , or 60 to 300 kg / m 3 It is possible to use lightweight aggregates with a low bulk density of 0.01 to 0.01 mm, the bulk density being determined in accordance with DIN EN 1097-3. Where the term "lightweight aggregates" (in the plural) is used below, these may be essentially chemically homogeneous or somewhat different lightweight aggregates. The term "lightweight aggregates" therefore also includes the term "lightweight aggregate".

[0058] In the context of the present invention, low particle strength means that it is less than 1 N / mm 2 The average particle strength is less than 1-5N / mm 2 High particle strength means 5N / mm 2 According to the method of the present invention, it is more than 1.0 N / mm 2 Lightweight aggregates having a low particle strength of less than 0.5 can also be used. The particle strength is determined in accordance with DIN EN 13055 (Annex C).

[0059] Suitable lightweight aggregates in the mixture include (with exemplary descriptions): Pumice: Pumice is a porous, glassy volcanic rock. It is produced during gas-rich volcanic eruptions by foaming of the magma released during the eruption. Such lightweight aggregates have, for example, average to high particle strength and a modulus of 400-700 kg / m 3 The bulk density is between 0.01 and 0.1.

[0060] Expanded clay: Expanded clay is a lightweight aggregate industrially produced from expanded clay. It is characterized, for example, by its rounded particle shape. It can be obtained, for example, by drying, crushing, expanding and firing the clay at about 1200 °C into small beads. Depending on the production, expanded clay has low to high particle strength and a modulus of 220 to 600 kg / m 3 The bulk density is between 0.01 and 0.1.

[0061] Expanded Shale: Expanded shale is a mineral lightweight aggregate made from natural raw shale by thermal treatment. It is characterized by a compact, flat or angular grain shape and is available with closed or open pore surfaces, depending on whether a crushing process is performed after combustion or not. Expanded shale has average to high grain strength and a hardness of 300 to 800 kg / m 3 It has a bulk density of.

[0062] Cinder: Cinder is a hard volcanic rock that is crushed and delivered according to the desired ratio. It has high particle strength and a density of 800-1000 kg / m 3 Volcanic bomb as bulk density of super.

[0063] Sintered hard coal fly ash: Sintered hard coal fly ash is produced during the combustion of dust-form hard coal in modern power plants. Granulation and subsequent sintering of the beads produces a lightweight aggregate with round grain shape and closed curved surfaces. Sintered hard coal fly ash has average to high particle strength and a solubility of 400-800 kg / m 3 The bulk density is between 0.01 and 0.1.

[0064] Bottom ash: Bottom ash is produced during the combustion of hard coal in dry-fired boilers of power plants. It is the sintered product of the non-combustible mineral components of hard coal, cooled in water. Bottom ash has an average particle strength and a viscosity of 400-800 kg / m 3 The bulk density is between 0.01 and 0.1.

[0065] Foam Glass: Foam glass is a completely inorganic, fibre-free, lightweight aggregate made from recycled glass. Waste glass is crushed into glass powder and fired at around 900°C. It is generally characterised by a round grain shape and a closed surface. Foam glass has low to average grain strength and a strength of 200 to 400 kg / m 3 The bulk density is between 0.01 and 0.1.

[0066] Expanded mica: Expanded mica is produced by heat treatment of mica schist, a mineral that belongs to the clay minerals and is produced by weathering. Expanded mica can be obtained, for example, by expanding vermiculite, and has low particle strength and a strength of 60-200 kg / m 3 The bulk density is between 0.01 and 0.1.

[0067] Expanded perlite: Expanded perlite is produced from thermally expanded coarse perlite. For example, coarse perlite particles with diameters of 0.2 mm to 1.2 mm can be rapidly heated to 800-1000 °C in a vertical furnace. The rock melts and the contained water evaporates at the same time. The viscous melt is expanded by the water vapor pressure to 10 to 20 times its initial volume and is very rapidly carried upwards in the hot reaction zone by a strong air current. The rapid cooling thus achieved solidifies the foamed melt into particles with a particle size of, for example, 0-5 mm. Expanded perlite has low particle strength and a melt strength of 50-300 kg / m 3 , especially 60-250kg / m 3 It has a bulk density of.

[0068] Prior to the expansion process, the perlite may be treated, in particular by adding a nitrogen source, in particular a nitride, with silicate, borate and / or phosphate glass, preferably in an amount of 2-3% by weight relative to the unexpanded perlite, to obtain expanded perlite.

[0069] In the thermal foaming process, it can be obtained from waste glass or a mixture of silicon oxide and crude perlite, respectively, and has a yield of 80-300 kg / m 3 Between 80 and 250 kg / m 3 Lightweight materials having bulk densities between 100 and 200 mm (respectively waste glass or silica / coarse perlite mixtures) can also be used.

[0070] Further suitable lightweight aggregates can be obtained from plant materials, such as wood, wool / chips, expanded corn (popcorn), expanded wood fibres and plant husks, in particular rice husks. They have a strength of up to 500 kg / m 3 It has a low bulk density of less than 1000000000.

[0071] Rice husk ash can also be used as a lightweight aggregate without further processing.

[0072] Despite the approval as lightweight aggregates according to DIN EN 13055-1, in particular expanded perlite and expanded mica, up to 250 kg / m 3 Lightweight aggregates having a bulk density less than 1000 MPa are currently not used in lightweight concrete, mainly because they have a very high absorption behavior during the mixing process due to at least partial destruction and the associated reduction in particle strength.

[0073] In particular, 40 to 1000 kg / m 3 , preferably 50 to 500 kg / m 3 Between 60 and 300 kg / m 3 Expanded perlite, expanded shale, expanded clay, expanded glass, rice husk ash, and mixtures thereof, having a bulk density of 1000 g / m2 or less, are particularly preferred as lightweight aggregates.

[0074] A concrete additive in the context of the present invention is an additive that is added in small amounts to a lightweight concrete mix, preferably prior to the preparation of the suspension mix, in order to improve the chemical or physical properties of the lightweight concrete mix or the properties of the lightweight concrete.

[0075] The concrete additive may be, for example, a concrete plasticizer, a plasticizer, an air entrainer, a sealant, a retarder, a set accelerator, a pressing aid, a hydrophobizing agent, a stabilizer, a fiber, or a shrinkage reducing agent.

[0076] Concrete additives highlighted are: As concrete plasticizers: polycarboxylates, especially polycarboxylic ethers, lignin sulfonates (also called lignosulfonic acids), melamine formaldehyde sulfonates, naphthalene formaldehyde sulfonates, hydroxycarboxylic acids and their salts. - surfactants as air entraining agents: for example surface-active substances based on modified natural products, e.g. wood rosin soap, - Hydrophobizing agents, such as siloxanes / alkylalkoxysilanes, fatty acids, fatty acid salts, polymers (synthetic resin dispersions), etc. Fibers with a fiber length of 2 to 18 mm. The fibers can be made of organic polymers (e.g. polyamides, e.g. aramids or polyolefins, e.g. polypropylene, etc.), glass, coal, steel, or basalt. Mixtures of different fibers can also be used, and fibers are used with lightweight aggregates. - filler materials in the form of rock powder (grain size less than 0.063 mm), particularly preferably in the form of limestone powder or quartz powder; - 2000kg / m 3 Filling materials in the form of rock particles with a size of 0-2 mm (grain size) with a gross density of at least 100% (according to DIN EN 12620 and DIN 1405-2). They are made of quartzite, greywacke, basalt, dolomite, volcanic rock, slate, reclaimed rock particles (according to DIN EN 12620:2008-07) and other materials. It may consist of:

[0077] Lightweight concrete is 200kg / m 3 ~1999kg / m 3 Depending on the ratio of lightweight aggregate to rock particles, and depending on the binder composition type and dosage and amount of water with respect to compressive strength, lightweight concrete can be made to be, for example, pumpable and sprayable.

[0078] The method for producing comprises a two-stage mixing: a first mixing to produce a binder suspension, and a second mixing comprising mixing the binder suspension thus produced with at least lightweight aggregate. The binder suspension comprises at least a binder mixture and water.

[0079] The (first) mixing with the high speed stirring tool differs from the (second) mixing with the low speed stirring tool in that the circumferential velocity during mixing with the high speed stirring tool is at least three times faster.

[0080] The first stage of mixing is carried out by means of a high-speed stirring tool, for example having a rotational speed of more than 100 U / min, in particular 150 U / min. The circumferential speed of the stirring tool is suitably between 3 and 20 m / s, preferably between 8 and 17 m / s.

[0081] The second stage of mixing is carried out by means of a low-speed stirring tool, for example having a rotational speed of less than 60 U / min, in particular less than 45 U / min, for example 15-25 U / min. The circumferential speed of the stirring tool is preferably between 0.9 and 1.25 m / s, preferably between 0.3 and 0.8 m / s.

[0082] The circumferential speed of the stirring tool in each case means the longest possible circumference, for example, when paddles of different lengths are used as stirring tools. If several stirring tools or stirring zones are present in the mixer, stirring tools with higher circumferential speeds or Froude numbers are relevant. The rotation speed of the stirring tool is a less suitable measure, since the mixing effect also strongly depends on the geometric shape of the stirring tool.

[0083] The dimensionless eigenvalues ​​due to William Froude, which specify a measure of the ratio between inertia and gravity and are commonly divided into supercritical (mixture acceleration > gravitational acceleration; Froude number greater than 1.0) and subcritical (mixture acceleration < gravitational acceleration; Froude number less than 1.0), are suitable for describing mixing.

[0084] The Froude number Fr is determined by the following mathematical relationship: Fr=ω 2 *r / g ω=2*π*n w=angular velocity in rad / sec r=radius in m g=m / s 2 The acceleration of gravity expressed as d=diameter n = number of revolutions per second and further solving the equation gives the result: Fr=d*n 2 *2*π 2 / g->2*π 2 / g=2*3.14 2 / 9.81=2.01->Fr=d*n*2.01

[0085] In a suspension mixer, the circumferential speed of the mixing tool is specified as: v=d*π*n and n=v / (π*d) So the following also works: Fr=v 2 *2 / (d*g)

[0086] The first mixing is in particular carried out such that the Froude number for producing a suspension mixture is greater than 10, preferably greater than 25, most preferably greater than 40.

[0087] The second mixing is in particular carried out such that the Froude number for producing a lightweight concrete mix is ​​less than 2, in particular less than 1.5.

[0088] The suspension mix preferably has a fluidity of at least F6. At the end of the second mix, the lightweight concrete mix preferably has a fluidity of at least F2, preferably at least F4.

[0089] Suspension mixers, sometimes also called colloid mixers, are suitable for the preparation of the suspension mixture, ie the first mixing.

[0090] The suspension mixer comprises a high-speed stirring tool, which preferably has a rotation speed of more than 300 U / min, in particular 800-2000 U / min. The circumferential speed of the stirring tool is suitably between 3 and 20 m / s, preferably between 8 and 17 m / s.

[0091] A particularly suitable suspension mixer is known from DE 10354888 B4, where it is referred to as a colloid mixer. In that respect, reference is made to the disclosure and definition of the suspension mixer in that document, which is therefore also the subject of this proprietary right. The suspension mixer has a two-part separation element comprising an upper premixing zone of larger volume and a lower dispersion zone of smaller volume, as well as a guide ring and a baffle plate that spatially limits the different zones from each other. The premixing zone and the dispersion zone each comprise a separate agitator. The agitating paddles of the dispersion zone press the mixed material against a baffle plate with a circular recess in the center, which is arranged above the agitating paddle zone of the dispersion zone. The mixed material then impinges on a guide ring arranged above the baffle plate, which has a smaller diameter than the baffle plate with respect to its outer and inner diameters. The mixed material is forced outwards and upwards along the guide ring and is thus forced into the premixing zone by a circumferential outer annular slit between the guide ring and the inner wall of the mixer. The mixed material then disintegrates in the center of the premixing zone so that it flows back through the guide ring, which is the first separating element seen from above, into the dispersion zone.

[0092] A further suitable suspension mixer with an upper circulation zone / premixing zone and a lower dispersion zone is known from DE 102011102988 A1, in which at least one mixing tool comprising a mixing shaft and a mixing paddle is first provided in the dispersion zone and then at least one separation element is provided which spatially separates the circulation zone and the dispersion zone from each other, the separation element opening at least one outer passage remote from the stirring shaft and an inner passage close to the stirring shaft, the inner passage achieving a material flow from the circulation zone in the dispersion zone and the outer passage achieving a material flow from the dispersion zone into the circulation zone, the outer passage being arranged above the plane of the mixing paddle, and at least the outer passage can be changed from the outer passage in its (total) passage surface during the mixing process.

[0093] For this purpose, the suspension mixer according to DE 102011102988 A1 preferably comprises two chambers (premixing zone and dispersion zone). The mixed material is passively moved in the mixing zone through the liquid mixed material outlet beyond the separation element, where the mixed material is initially sucked into the dispersion zone via the larger inlet in the dispersion element, preferably arranged above the rotation axis. The mixed material is captured there by the high-speed agitator and pushed radially outwards, preferably also upwards, so that in the flow direction the mixed material passes through the smaller openings of the separation disc or through the smaller openings between the outer edge of the dispersion disc and the wall of the vessel, respectively. The smaller openings are preferably arranged on the periphery of the separation disc. In this specification, smaller and larger refer to the relative area ratio of the smaller outlet openings and the larger inlet openings in the dispersion zone.

[0094] The second mixing involves mixing the suspension mixture produced in this manner with at least the lightweight aggregate. Free-fall mixers and cone mixers are suitable for this purpose if they are operated at low rotational or circumferential speeds, respectively.

[0095] Free-fall mixers are available in different installation sizes. As small devices with a capacity of a few liters, they are common in the DIY field and are also used partly in the commercial and industrial sector for use on construction sites. In industrial installation sizes with a volume of 0.5 square meters and more, they are used stationary in ready-mix concrete and prefabricated component factories. The basic principle is the same. The mixing process takes place in a rotatable drum. In the drum, the loading also takes place by means of a drum opening. A spiral or blade, fixedly installed in the drum wall, is attached to the inside of the drum and picks up a portion of the mixed material with each rotation.

[0096] Cone mixers have side scrapers on the lower cone wall and a central shaft containing an archimedes screw and / or inclined paddles fixed to the central shaft and / or a combination thereof. It narrows conically towards the bottom. This mixer type with a mixing chamber is characterized by the fact that due to the construction geometry, the mixed materials are transported from the bottom to the top during mixing, as well as being peeled off laterally from the screw / paddle and moving again to the bottom by free fall under the force of gravity.

[0097] The centrally located shaft / axle and scraper can be operated at different rotational speeds, so depending on the set rotational speed, the cone mixer can be operated at Froude numbers above 10 or above 25, and at Froude numbers below 2.5 or below 1.5.

[0098] In the case of the method according to the invention for producing a lightweight concrete mix, two different types of mixers or one mixer, respectively, are used in parallel and / or in succession, whereby the suspension mixture is mixed at a Froude number of more than 10 and rock particles and further materials are added if necessary, and the lightweight aggregates, even at low bulk density and particle strength, are subsequently homogenized with the remaining mixed materials in a manner that is gentle on the material, with a Froude number of less than 2.5.

[0099] According to a preferred embodiment, the lightweight concrete, when produced as a building element, has a coating layer on at least one, preferably both main faces (thus the two large surfaces of the building element). Prior to the introduction of the lightweight concrete according to the invention into the mould (e.g. formwork), a first layer of a different hydraulically hardening material, thinner compared to the lightweight concrete mixture according to the invention, can be introduced at a given application strength, onto which the lightweight concrete according to the invention is applied, connected and hardened. After the corresponding strength and / or hardening, a second layer of the same or different hydraulically hardening material, which is also connected to the lightweight concrete according to the invention, can be applied. As a result, elements coated on one and / or both sides with a coating layer can be easily, quickly and cost-effectively produced. The hydraulically hardening material can be a so-called plaster system, including plaster mortar.

[0100] Such a covering layer may consist, for example, of a hardened inorganic stucco binder, or even of a stucco binder slurry. Reinforcement, especially in the form of a fiber mat, may preferably be incorporated into the covering layer. The fiber mat may consist of glass fibers, carbon fibers, and / or basalt fibers. The fiber mat may first be provided in particular only at the end or flange area, respectively, of the building element in order to stabilize the flange.

[0101] It is likewise possible to insert fiber mats in advance in the manufacturing process before filling the formwork with the lightweight concrete mixture according to the invention, either for protection against shrinkage cracks and as a primer for subsequent coating, or to apply them after at least partial hardening, thus making it possible to carry out preparations in advance for subsequent surface treatment on both sides.

[0102] It is also possible to first introduce the lightweight concrete mix according to the invention, which as a lightweight concrete mix with the corresponding density and compressive strength can take on the static function of the building, into the formwork and then apply the low-density highly insulating lightweight concrete produced according to the invention to this compression-resistant lightweight concrete. To improve the adhesion between the different lightweight concretes, commercially available adhesion promoters can be applied, but it is also possible to work "wet-on-wet" and thus not use adhesion promoters. Again, it is equally possible to apply the compression-resistant lightweight concrete to the highly insulating lightweight concrete. As a result, a sandwich structure is formed, in which the compression-resistant lightweight concrete takes on the static protection function and the low-density highly insulating lightweight concrete takes on the thermal insulation and additional soundproofing.

[0103] By introducing different concrete densities in different parts of the building element, so-called gradient concrete can be produced; where higher density and compressive strength are statically required, concrete is used, and where insulation and / or weight reduction are required, lightweight concrete according to the invention is used; for example the transition between the different concrete types can generally be made continuously or wet-on-wet, respectively.

[0104] In the above-mentioned scheme, two layers of normal concrete of any concrete quality in terms of density and compressive strength can also be used, in which case the lightweight concrete according to the invention is applied in the first normal concrete layer in the respective desired layer thickness, and normal concrete of any concrete quality in terms of density and compressive strength is applied again as the last layer. The lightweight concrete according to the invention thus realizes the function of thermal insulation and / or additional sound insulation in this element of the sandwich structure, and the normal concrete realizes the static functional properties.

[0105] Moreover, a lightweight concrete, which has a lower density compared to normal concrete, is first introduced into the casting mould and then a commercial insulating material, e.g. a low density (<100 kg / m3 It is also possible to attach or insert mineral foam, mineral fiber insulation board, polyurethane insulation board, rigid foam board, polystyrene rigid foam board, cork board, wood fiber board, cellulose fiber board, wool, wood wool, etc., respectively, and again apply the lightweight concrete according to the invention on top of it, as well as permanently connect two lightweight concretes by means of a connecting means hardened in the concrete, the density and compressive strength of which may be different. The more compressively resistant lightweight concrete can take on a static function, for example as the inner shell of a sandwich facade.

[0106] Before the introduction of the lightweight concrete, supporting and static reinforcements can be introduced into the casting mould, which are also called supporting structures, as described in EP 0808959 B1. The above mentioned types of reinforcements are placed in the mould before the casting of the lightweight concrete according to the invention, are surrounded by said lightweight concrete and take on the desired functions after the hardening of the latter, as transport aids, static functions as well as connection and jointing aids on the structure.

[0107] Furthermore, all common support aids and connection means can be installed in the concrete, in which case they are introduced into the mould before filling it with the lightweight concrete and are trapped by it after pouring.

[0108] Before the introduction of the lightweight concrete into the mould, hollow bodies of any type can additionally be introduced in order to achieve an even further weight reduction of the building product made with the lightweight concrete according to the invention.

[0109] For accelerated and / or controlled hardening, the lightweight concrete can be transferred to a climatic chamber after pouring into a mold, in particular into a formwork, where the hardening climate can be set by hot air and / or hot steam, with respect to the temperature of the climatic chamber being set at 30-85°C, in particular 35-60°C, depending on the binder used. The hardening process can thereby be accelerated, for example in such a way that the lightweight concrete can also be removed from the mold after 4 hours.

[0110] 1200kg / m 3 In the case of the above-mentioned dry bulk density, the residual moisture of the lightweight concrete is preferably less than 16% by mass, particularly preferably less than 14% by mass, and further preferably less than 13% by mass.

[0111] Experimental Part In the examples, the following materials were used: Cement: CEM I 52, 5R, Holcim Cement: CEM I 42, 5R, Holcim Cement: CEM II BS 52, 5R, Holcim Cement: CEM III B 42, 5L-LH Aqua 4, Holcim Fly ash: HP, Baumineral Ground blast furnace slag: Holcim Bremen plant Microsilica: Silicoll P, manufactured by Sika Limestone powder (rock powder): Powder, manufactured by Bauminerale Hydrophobizing agent: Protec HWA(ST) HA-BE, from Ha-Be Betonchemie, Hameln, Germany (stearates) CaO (calcium oxide): WFK 11 / 6, Felswerke Plasticizer: PCE Powerflow 5101, MC-Bauchemie Plasticizer: ACE 430, manufactured by BASF Accelerator: Fastkick 111, manufactured by MC-Bauchemie Stabilizer: Centrament 520, MC-Bauchemie Blowing agent: SB 2, Mapei Activator: Sodium silicate: Impag Fiber: 6~18mm SikaFiber PPM-12, manufactured by Sika (micro polypropylene fiber) SRA: Shrinkage reducing agent: Centrament SRA 1. Manufactured by MC Bauchemie Rock particles with a grain size of 0-2 mm: sand from Manzke Baustoffe Rock particles with a grain size of 0-5 mm: gravel from Manzke Baustoffe Rock particles between 2 and 8 mm in size: gravel from Manzke Baustoffe Recycled brick chips 2-8mm: Manzke Baustoffe Lightweight aggregate 1: Expanded perlite with particle size of 0-5 mm, manufactured by Perliopol Lightweight aggregate 2: Fibo ExClay (expanded clay) with particle size of 2 to 5 mm

[0112] Unless otherwise stated, DIN EN 13055 and the test methods specified therein are used to determine the technical properties of the listed lightweight aggregates.

[0113] Experimental procedure The preparation of compositions 1 and 2 below was carried out according to DE 102011102988 A1 by first adding water to the suspension mixer (20 l = maximum mixing volume of the mixer), then turning on the agitator and adding cement, fly ash and concrete additives one after the other. Mixing was carried out in the suspension mixer with a Froude number of 48.3 (mixing paddle speed, circumferential speed of 8 m / s based on three rotating paddles) to form a suspension mixture within 240 seconds (from after cement addition). The suspension mixture had a fluidity of more than F6.

[0114] The suspension mixture was then directly charged into a free-fall mixer (Atika, 50 l = maximum mix volume of the mixer) into which the lightweight aggregate with water-hydrophobizing agent mixture (300 grams of water per kg of lightweight aggregate) had already been added and premixed with the fibers. The suspension mixture, lightweight aggregate 1 and fibers were mixed homogeneously in a free-fall mixer with a Froude number of 0.3 (0.5 revolutions per second of drum rotation). After 180 seconds (from the time of adding the suspension mixture) 30 l of lightweight concrete mixture was obtained.

[0115] The flowability was in each case defined by the slump classes F1 to F6 according to DIN EN 12350-5. The dry bulk density was measured in a heating cabinet at 105° C. according to DIN EN 12390-7. The water / binder value (W / B) is the ratio between the mass of water and the mass of binder, where limestone powder (if used), microsilica and CaO, e.g. fly ash, etc. were added to the binder.

[0116] Water for pre-wetting the lightweight aggregate is not included in the composition.

[0117] In the table below, 1000 liters / m 3 The shortfall was due to air voids in the lightweight concrete.

[0118] Composition 1 according to the experimental procedure above:

[0119] [Table 1]

[0120] The lightweight concrete mixture is The concrete produced in this way had a fluidity of F6 and a water-to-binder value of 0.32. The lightweight concrete produced in this way had a viscosity of 351 kg / m 3 Dry bulk density of 2.5N / mm 2 The average compressive strength of 0.095(W / m 2 The material had a thermal conductivity (lambda value λ) of 100 K.

[0121] Composition 2

[0122] [Table 2]

[0123] The lightweight aggregate was prepared according to the experimental procedure described above, except that it was added to the free-fall mixer first along with the fiber and rock particles.

[0124] The lightweight concrete mix had a fluidity greater than F6 and a water to binder value of 0.36.

[0125] The lightweight concrete produced by this method had a strength of 581 kg / m after 28 days. 3 Dry bulk density of 7.8N / mm 2 The average compressive strength was 1.01 g / g.

[0126] For compositions 3 and 4, the preparation was carried out according to DE 102011102988 A1 in such a way that water was first added (20 l) to a suspension mixer, the stirrer was started and the following were added in turn: a) Composition 3: Cement, fly ash, rock particles 0-2 mm, and concrete additives; b) For composition 4: cement, limestone powder, microsilica, and rock particles 0-2 mm, as well as concrete additives.

[0127] Mixing was carried out in a suspension mixer with a Froude number of 91.4 (mixing paddle speed, circumferential speed of 13 m / s) to form a suspension mixture within 240 seconds (from the time of cement addition), which had a fluidity greater than F6.

[0128] The suspension mixture was then charged directly into a free-fall mixer (Atika, 50 liters) to which rock particles 2-8 mm had already been added and premixed with the fibres. While continuing the mixing in the free-fall mixer, 50% of the suspension mixture was then added, followed by 50% of lightweight aggregate 1, then the remaining 50% of the suspension mixture, followed by the remaining lightweight aggregate 1. Mixing in the free-fall mixer was carried out at a Froude number of 0.3 (0.5 revolutions per second). After 240 seconds (after the addition of the suspension mixture) 30 liters of lightweight concrete mixture was obtained.

[0129] Composition 3:

[0130] [Table 3]

[0131] The lightweight concrete mix had a fluidity greater than F6 and a water to binder value of 0.40.

[0132] The lightweight concrete produced by this method had a strength of 1.214 kg / m after 28 days. 3 Dry bulk density of 28N / mm 2 The average compressive strength was 1.01 g / g.

[0133] Composition 4:

[0134] [Table 4]

[0135] The lightweight concrete mix had a fluidity greater than F6 and a water to binder value of 0.41.

[0136] The lightweight concrete produced by this method had a strength of 1.649 kg / m after 28 days. 3 Dry bulk density of 48N / mm 2 The average compressive strength was 1.01 g / g.

[0137] For compositions 5 and 6, the preparation was carried out according to DE 102011 102988 A1 in such a way that water was first added (20 l) to a suspension mixer, the stirrer was started and the following were added in turn: a) Composition 5: Cement, rock particles 0-2 mm, and concrete additives, and b) For composition 6: cement, fly ash, and concrete additives.

[0138] Mixing was carried out in a suspension mixer with a Froude number of 91.4 (mixing paddle speed, circumferential speed of 13 m / s) to form a suspension mixture within 240 seconds (after cement addition), which had a fluidity of >F6.

[0139] In the case of composition 5, 50% of the suspension mixture was then charged directly into a cone mixer (Kniele, 100 l = maximum mixing volume of the mixer) in which lightweight aggregate 2 had already been previously prepared and premixed with the fibres. The remaining 50% of the suspension mixture was then added, followed by lightweight aggregate 1, and the mixture was mixed homogeneously at a Froude number of 0.9 (1.2 screw revolutions per second) throughout the entire mixing. After 240 seconds (after the addition of the suspension mixture) 50 l of lightweight concrete mixture was obtained.

[0140] The lightweight concrete was placed in a curing chamber at 38°C to 43°C for 20 hours and then removed.

[0141] Composition 5:

[0142] [Table 5]

[0143] The lightweight concrete mix had a fluidity of F6 and a water to binder value of 0.44.

[0144] The lightweight concrete produced by this method had a strength of 1.275 kg / m after 28 days. 3 Dry bulk density of 34N / mm2 The average compressive strength was 1.01 g / g.

[0145] For composition 6, 50% of the suspension mixture was filled into a cone mixer (Kniele, 100 l = maximum mixing volume of the mixer) in which recycled brick chips had already been added and premixed with fibre and rock particles 0-2 mm, as described above. The remaining 50% of the suspension mixture was then added, followed by lightweight aggregate 1, and the mixture was mixed homogeneously at a Froude number of 0.9 (1.2 screw revolutions per second) throughout the entire mixing. After 240 seconds (after the addition of the suspension mixture), 50 l of lightweight concrete mixture was obtained. The lightweight concrete was filled into a mould and placed in a temperature-controlled curing chamber at about 40° C. for 20 hours, after which it was removed.

[0146] Composition 6:

[0147] [Table 6]

[0148] The lightweight concrete mix had a fluidity greater than F6 and a water to binder value of 0.42.

[0149] The lightweight concrete produced by this method had a strength of 1.551 kg / m after 28 days. 3 Dry bulk density of 42N / mm 2 The average compressive strength was 1.01 g / g.

[0150] For composition 7, water was first prepared in a suspension mixer (20 l) and ground blast furnace slag and activator were added according to DE 102011102988 A1. Both were premixed, followed by the addition of fly ash and concrete additives. Mixing was carried out in the suspension mixer with a Froude number of 91.4 (mixing paddle speed, circumferential speed of 13 m / s) to obtain a suspension mixture within 240 seconds (after the addition of ground blast furnace slag). The suspension mixture had a fluidity exceeding F6.

[0151] 50% of the suspension mixture was then charged to a cone mixer (Kniele, 100 liters) which already contained rock particles 2 along with fibre. With continued mixing, 50% of lightweight aggregate 1 was then added, followed by the remaining 50% of the suspension mixture, followed by the remainder of lightweight aggregate 1.

[0152] The mixture was mixed in a cone mixer at a Froude number of 0.9 (1.2 screw revolutions per second) for the entire time. After 240 seconds (after addition of the suspension mixture) 50 1 of lightweight concrete mixture was obtained. The lightweight concrete was filled into moulds and placed in a temperature controlled curing chamber at about 40° C. for 20 hours before being removed.

[0153] Composition 7:

[0154] [Table 7]

[0155] The lightweight concrete mix had a fluidity of greater than F6 and a water to binder value of 0.46. The lightweight concrete produced in this manner had a viscosity of 1.540 kg / m after 28 days. 3 Dry bulk density of 38N / mm 2 The average compressive strength was 1.01 g / g.

[0156] Composition 8 was prepared by first adding cement, rock particles 0-2 mm, limestone powder, concrete additives, fibers, and water, as well as concrete additives, in that order to a cone mixer (Kniele, 100 l = maximum mixing volume of the mixer), and then starting the agitator to mix uniformly for 180 seconds at a Froude number of 29.5 (7.0 screw revolutions per second). Lightweight aggregate 2 was then added at the same mixing speed and mixed for a total of 180 seconds. Lightweight aggregate 1 was then mixed uniformly with the components of the lightweight concrete mix within 240 seconds (after the addition of lightweight aggregate 1) at a Froude number of 0.9 (1.2 screw revolutions per second) to form the lightweight concrete mix.

[0157] The moulds were filled with lightweight concrete and placed in a temperature controlled curing chamber at approximately 40° C. for 20 hours, after which they were removed.

[0158] Composition 8:

[0159] [Table 8]

[0160] The lightweight concrete mix had a fluidity of F4 and a water to binder value of 0.42. The lightweight concrete produced in this manner had a viscosity of 1.489 kg / m after 28 days. 3 Dry bulk density of 31N / mm 2 The average compressive strength was 1.01 g / g.

[0161] Surprisingly, in a series of experiments it was found that in the production of lightweight concrete according to the invention, when CEM III B 42,5 cement, also including rock particles of up to 2 mm from the mix, was mixed with a Froude number of >100 during the preparation of the binder paste and the hardening of the produced product was carried out in a constant temperature chamber at 40°C, substantially identical strength values ​​were achieved in terms of early strength in the time range up to 24 hours and final strength after 28 days when the same amount of CEM III B 42,5 L cement was used instead of CEM I 52,5 R cement.

[0162] The strength increase compared to the mix without rock particles was 51% after 20 hours and 27% after 28 days.

Claims

1. A method for producing a lightweight concrete mix comprising at least the following steps: (A) combining at least water and a binder composition and mixing with a high speed stirring tool to obtain a suspension mixture; The binder composition comprises at least a cement or a geopolymer as a binder; the weight ratio of water to binder composition in the suspension mixture is from 1:5 to 1:1, in particular from 1:2 to 2:3; the binder comprises at least 40% by weight, preferably at least 50% by weight, of the binder composition; The binder is added as a powdered solid; Process, and (B) combining the suspension mixture or a portion of the suspension mixture with at least the lightweight aggregate or a portion of the lightweight aggregate and mixing with a low speed mixing tool to obtain a lightweight concrete mix; Lightweight aggregate: 40 to 1000 kg / m 3 , preferably 50 to 500 kg / m 3 , particularly 60 to 300 kg / m 3 and having a bulk density of The mixing with the high speed stirring tool is performed at a peripheral speed that is more than three times the peripheral speed of the mixing with the low speed stirring tool; Process A method comprising:

2. 2. The method according to claim 1, wherein the mixing with the slow stirring tool is carried out at a Froude number of less than 2.5, in particular less than 1.

5.

3. 3. The method according to claim 1 or 2, wherein the mixing with a slow stirring tool is carried out in a free-fall mixer or a cone mixer.

4. 4. The method according to claim 1, wherein the mixing with the high speed stirring tool is carried out at a Froude number of more than 10, in particular more than 25.

5. 5. The method according to any one of claims 1 to 4, wherein the mixing with a high speed stirring tool to obtain a suspension mixture is carried out in a suspension mixer.

6. 5. The method according to claim 1, wherein the mixing with a low-speed stirring tool and the mixing with a high-speed stirring tool are carried out in the same cone mixer and the same stirring tool in each case at different circumferential speeds in each case.

7. 7. The method according to any one of claims 1 to 6, wherein the binder is added only to the suspension mixture, and the binder composition is in particular added only to the suspension mixture.

8. 8. The method according to any one of claims 1 to 7, wherein initially 20 to 70% by weight, in particular 40 to 60% by weight, of the lightweight aggregate and 20 to 70% by weight, in particular 40 to 60% by weight, of the suspension mixture are subjected to mixing with a low speed stirring tool, and subsequently the remaining lightweight aggregate and the remaining suspension mixture are added in one or several stages by continuing the mixing with the low speed stirring tool.

9. 9. The method of any one of claims 1 to 8, wherein the water is provided first and the binder composition is added, preferably as a powdered solid, when the water and binder composition are combined.

10. 10. The method according to any one of claims 1 to 9, wherein the lightweight aggregate is initially provided when combining the suspension mixture or a portion of the suspension mixture with at least the lightweight aggregate or a portion of the lightweight aggregate.

11. To obtain a suspension mixture, a filler in the form of rock powder and / or rock particles 0-2 mm is added and mixing with a high-speed stirring tool is preferably carried out at a Froude number of more than 50, in particular more than 100, in particular for at least 30 seconds, particularly preferably for at least 60 seconds; The rock dust is preferably added to 1 m of the lightweight concrete mixture. 3 It is added in an amount of 50 to 150 kg per Rock particles 0-2 mm are preferably added to each cubic meter of the lightweight concrete mixture. 3 The method according to any one of claims 1 to 10, wherein the amount of the mixture is from 100 to 500 kg per kg.

12. 12. The method according to claim 1, wherein a plasticizer, preferably based on polycarboxylate, in particular on polycarboxylic ether, is added in an amount of 0.1 to 4% by weight, preferably 0.5 to 2% by weight, to obtain a suspension mixture.

13. 13. The method according to any one of claims 1 to 12, wherein no lightweight aggregate is added to obtain the suspension mixture.

14. A method according to any one of claims 1 to 13, comprising combining a suspension mixture having a fluidity of at least F6 with lightweight aggregate and mixing with at least 1% by weight, preferably 2-5% by weight, of lightweight aggregate.

15. 15. The method according to any one of claims 1 to 14, wherein 22 to 40% by weight of water is added to the suspension mixture.

16. 16. The method according to claim 1, wherein the lightweight aggregate has a particle size in the range from 0 mm to 6 mm, in particular a particle size of 0 to 2 mm, 0 to 3 mm, 3 to 5 mm or 2 to 8 mm as particle group, in each case according to DIN EN 13055.

17. 17. The method according to any one of claims 1 to 16, wherein the lightweight aggregate is selected from expanded perlite, expanded shale, expanded clay, expanded glass, waste glass, or a silica / crude perlite mixture, rice husk ash, and mixtures thereof, respectively.

18. 18. The method according to any one of claims 1 to 17, wherein a hydrophobizing agent is applied to the lightweight aggregate before it is contacted with the suspension mixture.

19. 19. The method according to any one of the preceding claims, wherein the lightweight aggregate is wetted with water, in particular by spraying, before being contacted with the suspension mixture.

20. 20. The method according to any one of the preceding claims, wherein the binder composition comprises ground blast furnace slag as binder additive, preferably in an amount of 60 to 80% by weight.

21. 21. The method according to any one of claims 1 to 20, wherein rock flour is added as filler with a particle size between 0.001 mm and 0.1 mm, preferably at most 0.063 mm, to obtain a suspension mixture.

22. 22. The method according to any one of claims 1 to 21, wherein the binder composition comprises fly ash as binder additive and cement as binder, the fly ash preferably comprising 10 to 60% by weight of the binder composition.

23. The binder composition comprises: - 2 to 25% by weight of alkali hydroxides and / or alkali silicates, and - 75 to 98% by weight of ground blast furnace slag, Or, - 2 to 20% by weight of alkali hydroxides and / or alkali silicates, and - 60 to 78% by weight of ground blast furnace slag, and - 20 to 38% by weight of fly ash 23. The method of any one of claims 1 to 22, wherein the geopolymer comprises:

24. The binder composition comprises microsilica as a binder additive and cement as a binder, the microsilica being present in a concentration of 30 to 50 kg / m in a lightweight concrete mix. 3 24. The method of claim 1, wherein the soluble soluble cellulose is added in an amount of about 1:

1.

25. 25. The method according to any one of claims 1 to 24, wherein the binder composition comprises rice husk fly ash prepared by grinding as a binder additive and cement as a binder, and the rice husk fly ash accounts for 10 to 60 mass% of the binder composition.

26. 26. The method according to any one of claims 1 to 25, wherein the caustic calcined CaO and the caustic calcined MgO are added in an amount of 1 to 5% by weight relative to the binder composition to obtain a suspension mix or a lightweight concrete mix.

27. 75-650 g / m for lightweight concrete mixtures 3 27. The method according to any one of claims 1 to 26, wherein graphene is added to the lightweight concrete mix, the graphene preferably having at least two or more graphene layers.

28. 28. The method according to any one of the preceding claims, wherein the lightweight concrete mix comprises rock particles with a particle size of 0.01 to 8 mm according to DIN EN 12620.

29. 29. The method according to any one of claims 1 to 28, wherein together with or after the addition of the lightweight aggregate, fibres of organic polymer, glass, coal, steel or basalt having a fibre length of 2 to 18 mm are added.

30. 30. The method of any one of claims 1 to 29, wherein an air entraining agent is added to the lightweight concrete mix.

31. A lightweight concrete mix obtainable according to the method according to any one of claims 1 to 30.

32. 32. A method for obtaining lightweight concrete by hardening a lightweight concrete mixture obtained according to the method of any one of claims 1 to 31, comprising the step of water hardening the lightweight concrete mixture as defined in any one of claims 1 to 31 in a mould.

33. 33. The method according to claim 32, wherein the lightweight concrete mix is ​​at least partially hardened in the mould into lightweight concrete in a climatic chamber at 30°C to 85°C, preferably at 35°C to 60°C.

34. Lightweight concrete: 250 to 1.999 kg / m 3 34. The method of claim 32 or 33, wherein the granules have a dry bulk density of

35. 35. The method of any one of claims 32 to 34, wherein the lightweight concrete has an A number greater than 500.

36. 36. The method of any one of claims 32 to 35, wherein the lower and upper layers in the mold have a higher density than the next successive or next further inwardly positioned layer.

37. 37. The method according to any one of claims 32 to 36, wherein an insulating or hollow body is introduced into the mould before or during filling of the mould with the lightweight concrete mix.

38. 38. The method according to any one of claims 32 to 37, wherein the lightweight concrete mix is ​​introduced into a mould in a block moulding machine and compacted by shaking and / or pressing to obtain lightweight concrete blocks therefrom.

39. 39. The method according to any one of claims 32 to 38, in which reinforcement and / or transport aids, in particular steel and / or textile reinforcement, are placed in the mould, preferably in each case before the introduction of the lightweight concrete mix.

40. 40. Lightweight concrete as a component obtainable according to the method of any one of claims 32 to 39.

Citation Information

Patent Citations

  • Method for producing a hydraulically setting building material suspension, and component produced with a hydraulically setting building material suspension

    DE102016013793A1

  • Production of combined materials of glass fiberr reinforced cement

    JP1977017508A

  • Production of concrete

    WO2002024425A1

  • Slurry mixer has upper agitation zone and lower dispersing zone, where dispersion zone has smaller volume than agitation zone

    DE102011102988A1

  • Colloidal mixers and methods for the colloidal preparation of a mixture

    DE10354888B4